Central American Biodiversity Conservation, Ecology, and a Sustainable Future - Huettmann, Falk (Springer New York : Imprint: Springer, 2015)
This book highlights key results and lessons learned from two field sites: La Suerte in Costa Rica and Ometepe in Nicaragua. The content within provides long term data on species abundance and distribution, with specific attention paid to primates of the region. Primates are flagship species and good indicators for the health of an ecosystem. Many primate species are sensitive to habitat alteration, and are often hunted out first. They also play an important role as seed dispersal agents for the regeneration of the forest. Central American Biodiversity compares results from these two field sites with regional trends to explore potential solutions. This book strongly calls for new approaches in conservation, making the case for looking beyond pure species biology and classic conservation, encouraging the reader to take into account the economic and political realities.